THE ECONOMIC REHABILITATION WITH GREENHOUSE DRYING SYSTEM OF COFFEE BEANS DURING PANDEMIC IN GAMPONG REULEUT TIMU, MUARA BATU DISTRICT, NORTH ACEH. - Tambarta, Emmia; Fadli; Suryadi; Bustami; Rizal (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2022)
Malikussaleh University (UNIMAL) as a state university in North Aceh has the potential in the form of human resources to play a role in village development. The idea of ​​a greenhouse system for drying coffee beans in Gampong Reuleut Timu was based on the condition of the Corona Virus Disease (COVID-19) Pandemic which dealt a tremendous blow to the economy of the village community. The majority of the people around the institution have house rentals for UNIMAL students. The best solution that academics offer is to turn into small and medium-sized entrepreneurs who can generate additional income. The community can take advantage of their free time by doing a coffee bean drying business with a greenhouse system which has a great opportunity to be developed considering the high intensity of sunlight in North Aceh Regency. The location of this activity is in Reuleut Timur Village, Muara Batu District, North Aceh Regency. The service activity was carried out in two stages, namely an explanation of how to make a greenhouse installation and an explanation of how to dry with a greenhouse system. The outputs are in the form of a service journal system International Review of Practical Innovation, Technology and Green Energy (IRPITAGE) Volume 1, Number 2, December 2021, online publications in the Merdeka News mass media, and an Agreement Document with Geuchik, Reulet Timu Village, Muara Baru District. North Aceh District.